The Validity of Story Media Equipped with Pictures to Improve Critical Thinking Skills and Student Learning Outcomes - Tutik Sri Rejeki; Sutarto Sutarto; Imam Mudakir (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
This research aims to test the validity of story media equipped with pictures to improve students' critical thinking skills and learning outcomes. This research is the research and development of the four-dimensional development model by Thiagarajan et al. (1974). Based on data analysis, the average assessment of the three validators on the material/content feasibility aspect was 95%, linguistics 96%, technical quality and design quality 93%, and development feasibility 91%. The average validation result for story media with images is 94%, which is in the very valid category. The average validation results of research validation instruments and the average validation results of learning tools are in the very valid category. The story media is equipped with images of the human respiratory system to improve critical thinking skills, and the student learning outcomes developed meet very valid criteria so they can be used in learning research to test their effectiveness and practicality.